2012
DOI: 10.4028/www.scientific.net/amr.455-456.796
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Support on the Hydrogenation of Ethyl Lactate over Ruthenium Catalysts

Abstract: The hydrogenation of biomass-derived ethyl lactate was studied over several ruthenium catalysts. The effect of support (TiO2, SiO2, γ-Al2O3, NaY and active-carbon) on the catalytic performance was evaluated. The ruthenium catalysts were characterized by inductively coupled plasma (ICP), N2 physisorption, powder X-ray diffraction (XRD) and transmission electron microscopy (TEM). The catalytic performance of the ruthenium catalysts is dependent on the intrinsic property of the support. Ru/SiO2 was found to be an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…The conversion of ethyl lactate was up to 98%, and the selectivity for 1,2-PDO was above 95% (10 h reaction time) (Table , entry 1) . Feng et al made an attempt to hydrogenate ethyl lactate over Ru catalysts supported on TiO 2 , SiO 2 , γ-Al 2 O 3 , NaY, and active carbon without addition of any promoters to simplify the catalyst preparation and thereby the cost of the process and found Ru/SiO 2 to be an efficient catalyst (Table , entry 4). , …”
Section: Catalytic Transformations Of Lactic Acid To Commodity Chemicalsmentioning
confidence: 98%
See 3 more Smart Citations
“…The conversion of ethyl lactate was up to 98%, and the selectivity for 1,2-PDO was above 95% (10 h reaction time) (Table , entry 1) . Feng et al made an attempt to hydrogenate ethyl lactate over Ru catalysts supported on TiO 2 , SiO 2 , γ-Al 2 O 3 , NaY, and active carbon without addition of any promoters to simplify the catalyst preparation and thereby the cost of the process and found Ru/SiO 2 to be an efficient catalyst (Table , entry 4). , …”
Section: Catalytic Transformations Of Lactic Acid To Commodity Chemicalsmentioning
confidence: 98%
“…Lactic acid or lactates can be converted to propylene glycol in the liquid phase over Ru catalysts with or without any promoters ,,, ,,,,, as well as over Co/SiO 2 or over Cu catalysts in the vapor phase. ,,, Pd, Ni, and Fe on SiO 2 as catalysts were studied by Huang et al, and Co/SiO 2 was investigated by Huang et al and Xue et al , A novel method of lactic acid hydrogenation by syngas over Au/ZrO 2 was discovered by Lei et al All catalysts reported in the literature for lactic acid hydrogenation and lactate hydrogenolysis are summarized and presented respectively in Tables and Table .…”
Section: Catalytic Transformations Of Lactic Acid To Commodity Chemicalsmentioning
confidence: 99%
See 2 more Smart Citations
“…The addition of some additives such as boron, tin, and iron to Ru-based catalysts has been reported in the literature [265]. Feng et al [266] hydrogenated ethyl lactate with Ru catalysts over TiO 2 , SiO 2 , Al 2 O 3 , NaY, and active carbon and found Ru/SiO 2 to be an effective catalyst [266][267][268]. Xu et al [264] tested the Co/SiO 2 catalyst for liquid-phase hydrogenation of ethyl lactate.…”
Section: Lactic Acid (La)mentioning
confidence: 99%